Looking for Earthquake Precursors From Space: A Critical Review - Picozza, Piergiorgio; Conti, Livio; Sotgiu, Alessandro (Frontiers in Earth Science, 2021)
Starting from late seventies, many observations have been reported about observations in space of signals reconciled with earthquakes and claimed as possible preseismic measurements. The detected parameters range from electromagnetic field components (in a large band of frequencies) to plasmas parameters; from particles detection to thermal anomalies; etc. Up to the DEMETER mission, the analyses have been carried out on datasets gathered by not devoted satellites. Even beyond the results obtained, the DEMETER mission has constituted a milestone for space-based investigations of seismo-associated phenomena drawing a baseline for next missions with respect instruments, observational strategy and measurements uncertainty. Nowadays, the CSES-01 satellite – developed within a sino-italian collaboration with the participation also of Austrian Institutes – represents the most advanced mission for investigating near-Earth electromagnetic environment aimed at extending the observation of earthquake precursors to a long time series. The benefit of the mission is even higher by considering that CSES-01 is the first of a program of several LEO small satellites, the second of which will be launched on 2023 with the same instruments and orbit of CSES-01, but with a shift of half of an orbit in order to monitor each trace twice per orbit. The article gives a short survey of space-based observations of preseismic phenomena from the early studies up to the more recent ones, critically reviewing results, hypotheses and trends in this research field. The supposed physical processes proposed to explain the observations are still unable to explain the large variety of the phenomenology, the statistical significance of the results are highly debated, and more in general a common consensus is still missing. Anyway, the investigation of the seismo-associated phenomena from space is a challenge for near future Earth observation.